Pelatihan Penulisan Karya Ilmiah sebagai Upaya Penguatan Literasi Akademik Mahasiswa S1 Keperawatan STIKES Medika Nurul Islam - Muhibuddin Muhibuddin (CV Abid Abadi Jaya, 2026)
The ability to write scientific papers is one of the academic competencies that students must possess as a provision to support research activities, complete studies, and develop academic culture in higher education. However, many students still experience difficulties in compiling scientific papers in accordance with academic principles, especially in formulating problems, developing writing systematics, using scientific language, and managing citations and references. This community service activity aims to improve the skills of undergraduate Nursing students at STIKES Medika Nurul Islam in compiling scientific papers through a structured training program. The implementation method uses a participatory approach consisting of preparation, implementation, and evaluation stages. The training was carried out through interactive lectures, demonstrations, writing practice, group discussions, and mentoring in the use of reference management applications. The results of the activity showed an increase in students' understanding of the principles of scientific writing, the ability to compile articles systematically, skills in using reference management applications, and increased critical, reflective, and collaborative thinking skills in the process of compiling scientific papers. In addition, the training also increased students' motivation and confidence to produce scientific works worthy of publication. Thus, scientific writing training has proven to be an effective strategy in strengthening academic competence, scientific literacy, and publication culture of students in the Medika Nurul Islam Health College environment.